Issues and challenges in implementing development charge : a case study of Manjung Municipal Council, Perak; and Sungai Petani Municipal Council, Kedah / Noor Amirah Hamzah and Nurulhuda Ali - Hamzah, Noor Amirah; Ali, Nurulhuda (2018)
Development charge is a charge imposed on any development of land or carried out in accordance with such changes at the prescribed rates due to local plans or local plan changes effect on changes in land use, density, and plot ratio or floor area in respect of any land. The amount of charge will be used in providing facilities and infrastructure in the local authority area. The aim of this research is to identify the issues and challenges in the implementation of development charge imposed by the local authority, and to recommend the solutions to those issues and challenges. This research uses the qualitative method of analysis to arrive at its findings. Interview sessions will be conducted through a semi-structured technique focused on two local authorities implementing the development charge in Perak and Kedah. All primary data is gathered from the respondents. Research findings revealed that there are (3) issues in which the imposition of rate has become the main issue in implementing development charge. The lack of knowledge by the applicant regarding the development charge has become a challenge for the local authority in implementing the development charge. The findings of this research may be of help to the relevant parties to get a better understanding about the practice of development charge in the states of Perak and Kedah.